2014
DOI: 10.1590/s1519-38292014000400009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of agreement between Visual Analogue Scales (VAS) and numerical questions to assess perception of teratogenic risks in treatment with drugs and radiotherapy in women

Abstract: Objectives: to evaluate the agreement between Visual Analogue Scales (VAS) and numerical questions as a way of assessing the perception of teratogenic risk of treatment with drugs and radiotherapy. Methods: the sample comprised 144 pregnant and 143 non-pregnant women consecutively recruited at public health centers in Porto Alegre, in the State of Rio Grande do Sul, from February to August 2011. The perception of risk for congenital malformations in the general population and the perceptions of teratogenic ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In their research, they concluded that there was no agreement between the two methods in estimating teratogenic risk. (Pons et al, 2014). Furthermore, it is recommended that future research exploring perceptions of teratogenic risk needs to utilize qualitative methods in addition to quantitative research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their research, they concluded that there was no agreement between the two methods in estimating teratogenic risk. (Pons et al, 2014). Furthermore, it is recommended that future research exploring perceptions of teratogenic risk needs to utilize qualitative methods in addition to quantitative research.…”
Section: Discussionmentioning
confidence: 97%
“…There is an ongoing debate on the utility of visual analogue scales in measuring risk perception. Some argue that responses of participants to questions including a visual analogue scale tend to cluster around the middle point of the scale and might over‐estimate the risk when it is low (Pons, Guimarães, Knauth, & Pizzol, 2014; Sanz et al, 2001), while others suggest that a visual analogue scale can provide a wide range of responses that can be chosen by research participants (Harland, Dawkin, & Martin, 2015). Pons et al investigated the level of agreement between a visual analogue scale and a numeric scale in estimating the teratogenic risk.…”
Section: Discussionmentioning
confidence: 99%